Diseminasi Pemanfaatan Limbah Menir Beras Sebagai Produk Etno-Spa Bedda Lotong Khas Suku Bugis-Makassar - Sumiati Sumiati; Andi Muhammad Irfan Taufan Asfar; Andi Muhammad Iqbal Akbar Asfar; Aisyah Nursyam; Andi Fauziah; Nurhasanah Nurhasanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Bedda Lotong is a powder made from roasted rice with spices that has been used for generations in the Bugis-Makassarese culture. Bedda Lotong used to be only used by the daughters of nobles, especially the descendants of Arung Paria and Bugis brides who were about to get married. However, the production of Bedda Lotong has begun to disappear and is only produced on a family scale which is carried out in a subsystem during spare time and is managed traditionally. The partnership program for the community focuses on promoting Bedda Lotong as a Bugis-Makassar ethno-spa. The activities carried out were in the form of counseling in the form of awareness of the benefits of Bedda Lotong, training and demonstrations on the processing of Bedda Lotong for partner groups, and mentoring. The results obtained from this partnership program are that the community is able to process rice groats and other ingredients into Bedda Lotong scrubs and a differentiation product, namely Bedda Lotong powder. The impact of this activity is the preservation of Tellu Sulapa Eppa culture through the manufacture of Bedda Lotong.